PENGARUH KOMITMEN ORGANISASIONAL, SISTEM PENGENDALIAN INTERN PEMERINTAH, DAN GAYA KEPEMIMPINAN TERHADAP KINERJA MANAJERIAL (Survey Pada SKPD Sumbawa Dan Sumbawa Barat) - Lukmanul Hakim; Thatok Asmony; Biana Adha Inapty (Master of Accounting Universitas Trunojoyo Madura, 2016)
This study was conducted to examine the effect of organizational commitment, the internal control system of government, and the leadership style of the performance of managerial work unit area in Sumbawa and Sumbawa Regency Government of West. The sampling technique used purposive sampling. The data were analyzed using multiple linear regression method. Results based on test data analysis showed that the p-value variable organizational commitment and internal control system of government has positive influence on managerial performance. While the leadership style variable did not show any effect on managerial performance. Based on the value of the F test showed that the variables of organizational commitment, the internal control system of government and leadership style were simultaneously had positive effect on managerial performance.